Efficiency of secondary traits in selecting for improved grain yield in extraearly maize under Strigainfested and Strigafree environments - Badu-Apraku, Baffour; Akinwale, R.; Oyekunle, M. (Wiley, 2014)
A base index involving Striga damage, number of emerged Striga plantsand ears per plant is used for selecting for maize (Zea mays L.) grainyield under Striga infestation. There are contradictory reports on the reliabilityof number of emerged Striga plants for selecting for Striga resistance.The objective of this study was to confirm reliability of thesecondary traits for selecting for improved grain yield under Striga infestation.Ten Striga-resistant extra-early cultivars were evaluated for3 years under artificial Striga-infested and Striga-free environments inNigeria. Analysis of variance combined across years and locationsshowed significant mean squares for genotype, year, location and theirinteractions for most traits. Sequential path analysis identified ear aspectas the only trait with significant direct effect on yield under artificialStriga infestation, while GGE biplot confirmed ear aspect, ears per plantand Striga damage as the most reliable traits. Ear aspect should beincluded in the base index for selecting for improved grain yield ofextra-early maize under Striga infestation, while the number of emergedStriga plants should be excluded.